The Effects Of Vardımon's System Functıonal Orthopedıc Magnetıc Applıance On Dentofacıal Structures In The Cases Wıth Class Iı Dıvısıon I Malocclusıon - Ömer Büyüksağın; Hüseyin Ölmez; Osman Bengi; Deniz Sağdıç; Yalçın Işımer (Galenos Yayinevi, 1996)
The purpose of our study is to examine the effects of Vardimon's system functional appliances with magnetic forces in orthodontic treatment approaches. In our study, 16 angular and 18 linear measurements were made on the initial and final radiographic pairs in 24 cases which 12 of them were treatment group and the other 12 were control group with Angle Class II Division I malocclusion. After the cephalometric evaluations it is seen that at the end of the functional orthopedic magnetic appliance of Vardimon's system treatment; the development of maxilla was reduced, the mandible was positioned inferiorly and anteriorly, the effective length of mandible was increased due to the increase in ramus height, Angle Class I canine and molar relationships were attained.